An improved switching control law for the optimized synchronous electric charge extraction circuit. (November 2015) - Liu, Weiqun; Badel, Adrien; Formosa, Fabien; Liu, Congzhi; Hu, Guangdi
Abstract: Nonlinear switching interface circuits are considered as an efficient way to improve the performance of vibration energy harvesters. Among the various approaches, OSECE (Optimized Synchronous Electric Charge Extraction) exhibits satisfying properties: simple switching strategy, good performance in low coupling cases and low load dependency. However, the overdamping induced by the voltage inversion at maximal points leads to performance degeneration in high coupling cases. This paper presents an improved switching control law for the OSECE technique. The new OSECE_PT (OSECE with switching Phase Tuning) technique presented here is to let the switches act ahead or after the maximal point with a phase tuning. Theoretical analysis and numerical simulations show that the OSECE_PT technique can improve the power performance effectively and preserves desired load independence properties.